2016
DOI: 10.1246/cl.160388
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photodynamic Properties of Graphene Quantum Dot Conjugated Ce6 Nanoparticles for Targeted Cancer Therapy and Imaging

Abstract: In this study, we report the enhanced photodynamic therapeutic (PDT) activity of Chlorin e6 (Ce6)-loaded graphene quantum dots (GQDs). GQDs reinforced the Ce6 loading, solubility, and fluorescence in aqueous media and enhanced ROS production and cancer cell death. This GQDs conjugated Ce6 could be a good platform for imaging-guided cancer therapy. Keywords: Graphene quantum dot (GQD) | Photodynamic therapy | Reactive oxygen species (ROS)Photodynamic therapy (PDT) is a light-sensitive cancer therapy that employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Photodynamic therapy is a light-sensitive cancer therapy that employs the cooperative interaction between light and photosensitiser to promote tumour suppression [ 95 , 96 ]. The cancerous cell is eventually killed under the correct conditions post-irradiation, as the photosensitizer overheats and essentially is self-terminated along with the neighbouring cells overexpressing hyaluronic acid receptors.…”
Section: Carbon Nanomaterials Conjugated With Hyaluronic Acid For Drug Deliverymentioning
confidence: 99%
“…Photodynamic therapy is a light-sensitive cancer therapy that employs the cooperative interaction between light and photosensitiser to promote tumour suppression [ 95 , 96 ]. The cancerous cell is eventually killed under the correct conditions post-irradiation, as the photosensitizer overheats and essentially is self-terminated along with the neighbouring cells overexpressing hyaluronic acid receptors.…”
Section: Carbon Nanomaterials Conjugated With Hyaluronic Acid For Drug Deliverymentioning
confidence: 99%
“…It displayed N‐binding dependent ROS generation and the PDT therapeutic effects. Nafiujjaman et al conjugated Ce6 to HA and further loaded it onto GQDs to develop a cancer cell‐targeted, imaging‐guided PDT nanosystems . The as‐prepared GQD‐HA‐Ce6 nanoparticles possessed a good biocompatibility, enhanced photosensitizer imaging detection, and excellent PDT under laser irradiation.…”
Section: Application In Bioimaging In Vitromentioning
confidence: 99%
“…Quantum dots are semiconductors with fluorescence properties that allow them to be used for real time drug delivery and as photosensitizers. With surface modification using tumor recognized molecules and drugs, quantum dots can move to target tumors and act as a supporting energetic agent in photodynamic therapy, a method that combines light and photosensitizers to generate oxygen species and promote tumor suppression [ 254 , 260 , 261 , 262 ]. Quantum dots are frequently used in a complex like with graphene and photosensitizer such as chlorin e6 [ 261 , 263 ].…”
Section: Application Of Alloy Nanoparticles In the Biological Fielmentioning
confidence: 99%
“…With surface modification using tumor recognized molecules and drugs, quantum dots can move to target tumors and act as a supporting energetic agent in photodynamic therapy, a method that combines light and photosensitizers to generate oxygen species and promote tumor suppression [ 254 , 260 , 261 , 262 ]. Quantum dots are frequently used in a complex like with graphene and photosensitizer such as chlorin e6 [ 261 , 263 ]. Martinenko et al reported that the complex ZnSe/ZnS quantum dots with chlorin e6 showed two-fold enhancement of photodynamic destruction in Ehrlich ascites carcinoma cells compared to that with free chlorin e6 molecules, and approximately 50% fluorescence resonance energy transfer from QDs to the chlorin e6 molecules [ 264 ].…”
Section: Application Of Alloy Nanoparticles In the Biological Fielmentioning
confidence: 99%